Market reform and school competition: The lesson from Sweden - Johan Wennström (Research Institute of Industrial Economics (IFN), 2016)
In a radical school choice reform in 1992, Sweden's education system was opened to private competition from independent for-profit and non-profit schools funded by vouchers. Competition was expected to produce higherquality education at lower cost, in both independent and public schools. This article analyzes whether the school choice reform was institutionally secured against school competition based on phenomena that are unrelated with educational quality. Interviews with key personalities reveal that the architects of the reform overemphasized the virtues of market reforms and therefore did not deem it necessary to establish appropriate rules and institutions for school competition. Instead, ill-conceived grading and curriculum reforms paved the way for moral hazard resulting in grade inflation and other forms of unintended school competition. The lesson from Sweden's experience is that market reforms of public services production, particularly those that introduce for-profit producers, must account for how institutions and incentive structures affect behavior.
Keywords: D02; D62; I28; 330; School choice; grade inflation; institutions; hazardous adjustment